Comparative efficacy of topical 5% 5-fluorouracil with electrosurgery in treatment of warts - Dogra Alka; Gupta Sunil; Bansal Amita (Wolters Kluwer Medknow Publications, 2006)
Warts are common dermatologicals disorder which are dificult to treat. In the present study the efficacy of topical 5% 5-fluorouracil was evaluated in various types of warts and compared with the conventional electrosurgical method which included both electrodessication and electrofulguration. 50 patients clinically diagnosed as warts were enrolled. 25 patients were treated with topical 5% 5-fluorouracil applied for 4 hrs twice daily for 3 weeks, while another 25 were treated with electrosurgery. It was observed that electrosurgery yielded better initial results than 5-fluorouracil (72 and 52% respectively), but at the end of 6 months, the results were favourable for 5-fluorouracil as compared to electrosurgery (44 and 36% respectively). This was due to the signficantly low recurrence rate with 5-fluorouracil in contrast to electrosurgery (8 and 48% respectively). Though electrosurgery yielded quicker initial results but 5-fluorouracil was better as long term measurer because of its significantly lower recurrence rates.